2016
DOI: 10.1111/cote.12254
|View full text |Cite
|
Sign up to set email alerts
|

3,3′‐Dinitrophenolsulphonephthalein: an acid–base indicator dye with unusual properties

Abstract: This paper is devoted to the phenolsulphonephthalein nitro derivative 3,3 0 -dinitrophenolsulphonephthalein, also called nitrophenol violet (NPV). The neutral molecular form, H 2 R, was isolated as a sultonic tautomer, and an X-ray crystal structure analysis was carried out. UV-vis absorption spectra in methanol, DMSO, acetonitrile, and water at different pH values were ascribed to the molecular and anionic (H 2 R, HR À , and R 2À ) species. Whereas the pK a values of this acid-base indicator (HR À ¡ R 2À + H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The absorption band of the dianion R 2of the corresponding triphenylmethine dye of 3,3'-dinitrophenolsulfonepht halein (6) in aqueous media is characterised by the values λ max = 568 nm and ε max = 72 × 10 3 L/mol/cm (Scheme 4). 12 In our case, the molar absorptivity is much lower (ε = 36 × 10 3 L/mol/cm), and the absorption band is very broad. This is evidently caused by two additional oxygen atoms and negative charges.…”
Section: 5-dinitrosulfonefluoresceinmentioning
confidence: 49%
See 1 more Smart Citation
“…The absorption band of the dianion R 2of the corresponding triphenylmethine dye of 3,3'-dinitrophenolsulfonepht halein (6) in aqueous media is characterised by the values λ max = 568 nm and ε max = 72 × 10 3 L/mol/cm (Scheme 4). 12 In our case, the molar absorptivity is much lower (ε = 36 × 10 3 L/mol/cm), and the absorption band is very broad. This is evidently caused by two additional oxygen atoms and negative charges.…”
Section: 5-dinitrosulfonefluoresceinmentioning
confidence: 49%
“…The dyes used in the present study were prepared and characterised previously: 4,5-dinitrosulfonefluorescein, 2,4,5,7 -tetranitrosulfonefluorescein, and sulfonefluorescein, 11 3,3' -dinitrophenolsulfonephthalein, 12 3,3',5,5'-tetranitrophenol sulfonephthalein, 13 2,4,5,7-tetranitrofluorescein. 10,14 Cetyltrimethylammonium bromide (CTAB) was from Sigma (99%).…”
Section: Methodsmentioning
confidence: 99%
“…Naturally, the visual absorption bands of anions 17 and 18 in aqueous alkali are similar to those of the R 2− anions of 3,3′‐dinitrosulphonephthalein (nitrophenol violet) and 3,3′,5,5′‐tetranitrosulphonephthalein (nitrophenol crimson), at λ = 568 nm and 558 nm , respectively. Moreover, quantitative studies demonstrated that the nucleophilic attack of HO − , which results in carbinol formation, occurs much more quickly in the case of nitrophenol crimson .…”
Section: Resultsmentioning
confidence: 71%
“…The current article aims to further examine TNF, thus enhancing previous research and simultaneously extending the research into the series of nitro‐substituted triphenylmethine and xanthenes dyes . In particular, the transformations of TNF in highly basic media were examined using electrospray spectroscopy and X‐ray analysis.…”
Section: Introductionmentioning
confidence: 99%
“…the same effect as four Br atoms. Analogous conclusion may be made when comparing the pK a a2 values of 3,3 ,5,5 -tetrabromo sulfonephthalein (indicator bromophenol blue) and 3,3 -dinitro-sulfonephthalein (nitrophenol violet) both in water and dimethyl sulfoxide [77]. Therefore, the dramatic increase in the pK a a1 and decrease in the (pK a a2 − pK a a1 ) of 4,5-dinitro derivatives ( As result, the negative contribution of the term log α H 2 Q is substantial.…”
Section: Dependence Of the Ratio Of The Values Of The Stepwise Ionizamentioning
confidence: 60%